Is acceptance and commitment therapy helpful in reducing anxiety symptomatology in people aged 65 or over? A systematic review - Delhom, Iraida; Mateu-Mollá, Joaquín; Lacomba-Trejo, Laura (Frontiers in Psychiatry, 2022)
Anxiety-related mental health problems constitute a health challenge, especially in the elderly population. At present, there are few psychological treatments to reduce anxiety adapted to this group. The aim of this study was to conduct a systematic review of the literature to determine the therapeutic effects of Acceptance and Commitment Therapy (ACT) on anxiety in older adults, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Two blinded reviewers participated in the search, selection and methodological quality assessment processes; reaching satisfactory levels of agreement between reviewers (κ > .70). The search was performed in PubMed, Proquest Central, Scopus and Web of Science; making use of standardised terms for the construction of the algorithm. In the general search 348 studies were found. After applying the eligibility criteria and excluding duplicates, seven articles were extracted for qualitative analysis. The total number of subjects was 633, with an average age of 68.89 years (68.94% women). The analysis of methodological rigour showed moderate indices on average. The publications focused primarily on samples with a diagnosis of generalised anxiety disorder, proposing a variety of assessment tests for related dependent variables, especially depressive symptoms and psychological flexibility. Critical analysis of the findings provides evidence for the efficacy of ACT in reducing anxious and depressive symptoms in older adults. This study proposes the use of this procedure as a non-pharmacological alternative for a group usually underrepresented in the scientific literature on this topic.